2019
DOI: 10.1021/acsami.8b14877
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Carbon Dots with Innovative NIR-II Emission for in Vivo Renal-Excreted Optical Imaging and Photothermal Therapy

Abstract: Carbon dots (CDs) with low biotoxicity, high photostability, and wellcontrolled size are highly desirable imaging agents for optical bioimaging. However, most of the CDs triggered by ultraviolet/blue light present visible/first near-infrared emissions shorter than 820 nm, impairing their imaging applications in vivo by low penetration depth. Hence, developing novel CD-based materials with second nearinfrared (NIR-II) emission located in 1000−1700 nm region is an urgent task. Here, a novel NIR-II-emitting CD-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(169 citation statements)
references
References 49 publications
1
163
0
Order By: Relevance
“…The ease of modification, low toxicity, and most importantly, outstanding FL properties make BCDs ideal drug delivery vehicles. Except transport drug molecules into cells, BCDs can also serve as bioimaging agents . In the past few years, many research groups have used a variety of raw materials to prepare a wide variety of BCDs for bioimaging.…”
Section: Applications Of Bcdsmentioning
confidence: 99%
“…The ease of modification, low toxicity, and most importantly, outstanding FL properties make BCDs ideal drug delivery vehicles. Except transport drug molecules into cells, BCDs can also serve as bioimaging agents . In the past few years, many research groups have used a variety of raw materials to prepare a wide variety of BCDs for bioimaging.…”
Section: Applications Of Bcdsmentioning
confidence: 99%
“…This blue supra-CDs exhibited a broad absorption peak in the NIR region which is responsible to the high photothermal conversion efficiency 52%) under 732 nm laser of 0.5 W cm −2 . Li et al [157] showed the CDs from the biomass-watermelon, which showed the NIR II imaging and photothermal conversion efficiency of 30.6% triggered by laser of 808 nm. It is well known that the d orbits of Cu(II) can split under the ligand field with specific geometry, generating higher degenerate e.g.…”
Section: Fluorescent Cds Conjugated With Photothermal Therapeutic (Ptmentioning
confidence: 99%
“…Not only photodynamic therapy, also photothermal therapy (PTT) has been proven to induce irreversible damage to many cancer cell types [96]. CDs can be used as potential photothermal agents since they can induce enormous temperature changes under irradiation [8].…”
Section: Carbon Dots As Photothermal Agentsmentioning
confidence: 99%